A redescription of Leucothoe spinicarpa (Abildgaard, 1789) based on material from the North Atlantic (Amphipoda: Leucothoidae) - Crowe, Stacie E. (Zootaxa, 2006)
The identification of Leucothoe spinicarpa (Abildgaard) has presented a problem for taxonomists in recent years as it is widely regarded to be part of a species complex with cosmopolitan distribution. In an attempt to clarify the status of this species, a neotype of Leucothoe spinicarpa is herein designated and a complete redescription of the species given.